2020
DOI: 10.1017/jlg.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-regional differences in the social perception of allophonic variation: The evaluation of [tʃ] and [ʃ] in Huelva and Lepe (Western Andalucía)

Abstract: This study examines the social perceptions of the traditional Andalusian feature [ʃ] and the Castilian feature [tʃ] in the city of Huelva and the town of Lepe in Western Andalucía, Spain. A matched-guise experiment was created by digitally manipulating spontaneous speech from twelve Western Andalusian speakers, varying only in word-medial syllable-initial [tʃ] and [ʃ] for <ch> in disyllabic words. Based on 221 listeners from Huelva and Lepe, mixed effects linear regression models indicate that listeners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…is algorithm is important in this platform's data analysis since it can properly evaluate a vast amount of data information. (2) Complete the innovation service platform for small, medium-sized, and micro firms and further describe the services offered by the innovation platform, in accordance with the core principles for constructing the platform. After a year of official usage of the service innovation platform for small, medium-sized, and micro firms, assess its real utility and demonstrate the platform's benefits based on the findings [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is algorithm is important in this platform's data analysis since it can properly evaluate a vast amount of data information. (2) Complete the innovation service platform for small, medium-sized, and micro firms and further describe the services offered by the innovation platform, in accordance with the core principles for constructing the platform. After a year of official usage of the service innovation platform for small, medium-sized, and micro firms, assess its real utility and demonstrate the platform's benefits based on the findings [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, social perception has advanced rapidly. To begin, sensor perception is employed in the environment to allow intelligent devices to fully utilise the perception data obtained in order to construct human-computer interaction [ 2 ]. Secondly, after entering the era of big data, people's lives are full of data and information.…”
Section: Introductionmentioning
confidence: 99%
“…As such it is inseparable from the ideological field and can be seen as an embodiment of ideology in linguistic form" (Eckert 2008, p. 464). The multitude of social meanings 8 attached to linguistic variants has been supported by several sociolinguistic perception studies, where the manipulation of a single phonetic variant (Barnes 2015;Campbell-Kibler 2007Chappell 2016Chappell , 2018Chappell , 2019Chappell , 2020Chappell , 2021aRegan 2020Regan , 2022bRegan , 2022cWalker et al 2014;Wright 2021aWright , 2021b or of a single word (Baird et al 2018;Regan 2022a) between guises affects listeners' evaluations. Other sociolinguistic perception studies have examined the indexical fields of language varieties 9 (Callesano and Carter 2019;Carter and Callesano 2018;Chappell and Barnes 2023;Niedzielski and Preston 1999), demonstrating that speech perception research can further our understanding of the social meaning of language varieties as well.…”
Section: Social Information In Speech Perceptionmentioning
confidence: 97%
“…It has been shown that linguistic information affects social perceptions of speakers (Barnes 2015;Campbell-Kibler 2007;Chappell 2016;Regan 2022c;Walker et al 2014;Wright 2021a) and that social information affects linguistic perception as well (Barnes 2019;Hay et al 2006aHay et al , 2006bHay and Drager 2010;Koops et al 2008;Niedzielski 1999). For example, subtle differences in linguistic information, 2 such as hearing affricate [t ] or fricative [ ] for the voiceless prepalatal /t / in Andalusian Spanish (Regan 2020), can affect the social perception 3 of the speaker. Social information, such as implied speaker nationality (Hay et al 2006a;Niedzielski 1999) or implied speaker ethnicity (Rubin 1992;Gutiérrez and Amengual 2016), has also been found to affect social perception and/or linguistic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the probably apocryphal and exaggerated nature of the Shibboleth story, there is evidence that individuals treat others preferentially based on pronunciation within languages [4][5][6][7][8], even when only two phonetic variables are compared [9]. Previous research has repeatedly demonstrated that individuals across cultures display in-group preferences-that is, people prefer to cooperate with individuals with whom they believe they share similarities ('parochial altruism,' see [10][11][12][13][14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%